Management of Facilities and Infrastructure Development for Educators and Education Personnel at MTsN 11 Majalengka - Makalao, Dwi Ajeng Maulidya; Diana, Aan; Salshabila, Dian; Khana, Muhammad Amar (IAIN Manado, 2024)
Management of Facilities and Infrastructure Development for Educators and Education Personnel at MTsN 11 Majalengka. This study aims to comprehend and assess facilities and infrastructure management at MTsN 11 Majalengka. Although management has been performing well, several issues must be addressed. These issues include a need for more papers from the principal and a need for computer facility maintenance. The learning process needs to be improved as a result of this mismatch. The study employs a qualitative technique as well as a descriptive strategy. The principal, staff, and subject teachers' data and management of educational facilities and infrastructure can yield benefits. The facility and infrastructure management of MTsN 11 Majalengka has been working smoothly. However, there are still some issues that need to be improved